The joint Simon effect depends on perceived agency, but not intentionality, of the alternative action - Stenzel, Anna; Dolk, Thomas; Colzato, Lorenza S.; Sellaro, Roberta; Hommel, Bernhard; Liepelt, Roman (Frontiers in Human Neuroscience, 2014)
A co-actor’s intentionality has been suggested to be a key modulating factor for joint action effects like the joint Simon effect (JSE). However, in previous studies intentionality has often been confounded with agency defined as perceiving the initiator of an action as being the causal source of the action. The aim of the present study was to disentangle the role of agency and intentionality as modulating factors of the JSE. In Experiment 1, participants performed a joint go/nogo Simon task next to a co-actor who either intentionally controlled a response button with own finger movements (agency+/intentionality+) or who passively placed the hand on a response button that moved up and down on its own as triggered by computer signals (agency-/intentionality-). In Experiment 2, we included a condition in which participants believed that the co-actor intentionally controlled the response button with a Brain-Computer Interface while placing the response finger clearly besides the response button, so that the causal relationship between agent and action effect was perceptually disrupted (agency-/intentionality+). As a control condition, the response button was computer controlled while the co-actor placed the response finger besides the response button (agency-/intentionality-). We observed a JSE when the co-actor responded intentionally and the causal relationship between co-actor and action effect could be perceived, but not when the co-actor did not respond intentionally and the causal relationship was disrupted (Experiment 1). When the intentionality of the co-actor was maintained but the perception of the causal relationship between co-actor and action effect destroyed, the JSE was absent (Experiment 2). Our findings clearly indicate a vital role of a co-actor’s agency for the JSE and suggest that the ascription of agency is strongly perceptually grounded.